2000
DOI: 10.1002/1097-4598(200009)23:9<1348::aid-mus5>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fatigue induced by stimulation with and without doublets

Abstract: Muscles are usually stimulated by shocks delivered at some constant rate. However, human thenar motor units generate optimum force per pulse when excited by impulse trains that begin with one or two short interpulse intervals (“doublets”), followed by longer intervals. Our aim was to determine whether the rate of force and force–time integral reduction during fatigue of thenar muscles is influenced by an initial doublet, and/or the number of pulses per train. We first matched thenar force–time integral using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 20 publications
3
65
4
Order By: Relevance
“…This phenomenon is often called "muscle wisdom" (157,179). In addition, impulse trains in vivo typically begin with groups of closely spaced impulses (doublets), which appear to enable force production with less associated fatigue (54), likely because of the force potentiation occurring with the closely spaced impulses (1), which gives more effective force production for a given number of APs.…”
Section: Decreasing Firing Ratementioning
confidence: 99%
“…This phenomenon is often called "muscle wisdom" (157,179). In addition, impulse trains in vivo typically begin with groups of closely spaced impulses (doublets), which appear to enable force production with less associated fatigue (54), likely because of the force potentiation occurring with the closely spaced impulses (1), which gives more effective force production for a given number of APs.…”
Section: Decreasing Firing Ratementioning
confidence: 99%
“…In terms of inferring the nature of the motor command, although the VAL technique has been shown to be a reliable technique to assess descending commands 40 and central fatigue 19,60 , this method presents some limitations. Indeed, some authors suggested that VAL overestimates maximal muscle activation [61][62][63] .…”
mentioning
confidence: 99%
“…Muscle training can certainly help, but also has the potential for unwanted slowing [17]. Since both fatigue in the short term and slowing in the longer term is correlated to the number of pulses delivered to the neuromuscular system [21], [14], [28], [30], optimal patterns of stimulation have been investigated in a variety of applications with the aim of eliciting a desired force output with the minimum number of pulses [4], [12], [18], [20], [22], [3]. A possible approach to determine optimum patterns of stimulation is to maximize the force-time integral (FTI) per unit impulse (FTIpP) of the elicited isometric contractions.…”
mentioning
confidence: 99%